Red cell and platelet transfusion burden following myeloablative allogeneic haemopoietic stem cell transplantation. Issue 12 (December 2015) - Le Viellez, A.; P'Ng, S.; Buffery, S.; Wright, M.; Cooney, J.; Cannell, P.; Purtill, D.
Abstract: Background: Adult allogeneic haemopoietic stem cell transplant (HSCT) usually requires blood transfusion support of red cells and platelets. There are few studies describing transfusion burden after allogeneic HSCT. Aims: This study aims to quantify and identify determinants of transfusion burden after allogeneic HSCT to improve planning, inventory management and patient counselling. Methods: A retrospective audit of blood use (red cells and platelets) of all adult HSCT ( n = 169) was performed over an 8‐year period extracted from pathology and hospital databases. ABO compatibility, graft type, conditioning regimens and patient factors were analysed for up to 12 months post transplant. Results: Transfusion burden was lower than expected and lower than reported by other groups. The median number of units transfused was four red cells and four platelets by day 30, and six red cells and six platelets by day 365. The median time to transfusion independence was 12 days for red cells and 16 days for platelets. Factors associated with increased red cell use included sex, disease stage, graft type (cord blood) and ABO compatibility. Disease stage and graft type (cord blood) were associated with increased platelet transfusion. Conclusions: Donor and patient characteristics are associated with transfusion burden after allogeneic HSCT. Determining transfusion burden in HSCT and identifying determinants of increased transfusion use assist in inventory planning and patient information.